2020
DOI: 10.2147/ijn.s255874
|View full text |Cite
|
Sign up to set email alerts
|

<p>ICG-Loaded PEGylated BSA-Silver Nanoparticles for Effective Photothermal Cancer Therapy</p>

Abstract: Purpose Indocyanine green (ICG), a near infrared (NIR) dye clinically approved in medical diagnostics, possesses great heat conversion efficiency, which renders itself as an effective photosensitizer for photothermal therapy (PTT) of cancer. However, there remain bottleneck challenges for use in PTT, which are the poor photo and plasma stability of ICG. To address these problems, in this research, ICG-loaded silver nanoparticles were prepared and evaluated for the applicability as an effective age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Most importantly, albumin can extend the plasma circulation time of the coated NPs by itself, while other coating materials usually require further PEGylation to ensure sufficient plasma residence. Previously, we reported that BSA-coated Silver NPs could reside in the bloodstream for about an hour without any other modification [ 36 ]. In addition, due to albumin’s propensity to bind with different types of drug molecules and materials (such as fatty acids), the BSA-coated NPs can serve as effective drug carriers [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, albumin can extend the plasma circulation time of the coated NPs by itself, while other coating materials usually require further PEGylation to ensure sufficient plasma residence. Previously, we reported that BSA-coated Silver NPs could reside in the bloodstream for about an hour without any other modification [ 36 ]. In addition, due to albumin’s propensity to bind with different types of drug molecules and materials (such as fatty acids), the BSA-coated NPs can serve as effective drug carriers [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is so because, by focally irradiating an external laser to the tumor site, spatially selective and minimally invasive treatment could be accomplished. The therapeutic effects of PTT heavily rely on the light-to-heat conversion efficiency of the photothermal agents, as well as on the accessibility of the tumor tissue to the laser [ 36 ]. Therefore, to date, various NPs composed of different materials, including silver NPs, have been explored in the PTT research [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Ag NPs are cytotoxic [ [16] , [17] , [18] ] i.e. they cause cell membrane damage [ 19 ], DNA damage [ 20 ], oxidative stress [ 21 ], and the formation of reactive oxygen species (ROS) [ 22 ]. Staphylococcus aureus ( S. aureus ) is the most common type of bacterium that causes skin infection [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional tumor therapy, both photothermal and photodynamic therapy can be applied accurately and effectively with less side effects and greatly reduce the patient's pain in a noninvasive way (Figure 2) (Li et al, 2020). Photothermal agents are materials with good light-to-heat conversion capabilities, mainly including noble metals (gold (Wang et al, 2013), silver (Park et al, 2020), platinum (Ma et al, 2020), etc. ), two-dimensional materials (graphene (Chen et al, 2016), black phosphorus (BP) (Geng et al, 2019), transition metal-based materials (Xie et al, 2019), etc.…”
Section: Nanomaterials Used In Photothermal Therapy and Photodynamic ...mentioning
confidence: 99%